Genetic evidence strongly support an essential role for PfPV1 in intra-erythrocytic growth of P. falciparum. - Trang Chu; Klaus Lingelbach; Jude M Przyborski (PLoS ONE, 2011)
Upon invading the host erythrocyte, the human malaria parasite P. falciparum lives and replicates within a membrane bound compartment referred to as the parasitophorous vacuole. Recently, interest in this compartment and its protein content has grown, due to the important roles these play in parasite egress and protein traffic to the host cell. Surprisingly, the function of many proteins within this compartment has not been experimentally addressed. Here, we study the importance of one of these proteins, termed PfPV1, for intra-erythrocytic parasite survival. Despite numerous attempts to inactivate the gene encoding PfPV1, we were unable to recover deletion mutants. Control experiments verified that the pv1 gene locus was per se open for gene targeting experiments, allowing us to exclude technical limitations in our experimental strategy. Our data provide strong genetic evidence that PfPV1 is essential for survival of blood stage P. falciparum, and further highlight the importance of parasitophorous vacuole proteins in this part of the parasite's life cycle.